A New Avenue to One-Pot Four-Component Synthesis of Spiro[indoline-3,4′-quinoline] Derivatives Using DABCO as a Green Catalyst - Maury, Suresh Kumar; Singh, Sundaram (Synthesis, 2022)
A simple, efficient, and green, one-pot four-component synthesis of spiro[indoline-3,4′-quinoline] derivatives has been developed from isatin, ethyl cyanoacetate/malononitrile, dimedone, and aniline using green catalyst DABCO and green solvent ethanol. The current method generates good to exceptional yields in a short reaction time and provides a broad substrate scope. This method also works for gram-scale reactions.
Keywords: DABCO; spiro[indoline-3,4′-quinoline] derivatives; isatin; ethyl cyanoacetate; malononitrile; dimedone; anilines